KOMPETENSI KEPRIBADIAN GURU DAN DISIPLIN BELAJAR SISWA PADA MATA PELAJARAN AQIDAH AKHLAK - Anis Fauzi, Iis Herlina (IAIN Ambon, 2019)
ABSTRACT: The issues raised in this study are weaking teacher’s personalitycompetence is seen from the phenomenon that many teachers are not optimal in implementing the standards process, just do the job from leadership. And there are many students who are not disciplined in learning. This research was conducted at MA Darul Huda Mandalawangi – Pandeglang. With the object of the research arestudents in the madrasah. This research used survey research method by the primary data collection that used the questionnaire. Selection of samples tested in this research 78 respondents as the sample of MA. Hypothesis testing usedSPSS V.16 for windows.Hypothesis test done / conducted by using themultiple regression coefficient. Result of the research were: First, a significant positive influence from teacher’s personality withlearning result have influence of 42,8%; Second, a significant influence from student learningdiscpiline with learning result have influence of 41,3%; Third, a significant influence from teacher’s personality and student learningdiscipline with learning result both have influence of 51,5% to learning result. Based on the result of this research is expected to be good contribution for the implementation of learning aqidah akhlak up to the goal.